How do I solve 4x + 3y=0 & 2x + y = -2 using substitution

4x + 3y = 0

2x + y = -2

take 2x and subtract to the side with -2

it’ll look like this: y = -2x - 2

plug that equation in where the y is in the other equation.

it’ll look like this: 4x + 3(-2x - 2)=0

which you multiply 3 and the -2x and the -2

which the equation would be: 4x - 6x - 6=0

put together like terms: -2x - 6=0

add the 6 to the side with the zero: -2x = 6

divide both sides by -2 which x= -3

to get y you plug in the answer for x (-3)

2(-3)+y= -2

so it’d then be -6 + y = -2

add the -6 to the side with -2

y= -2 +6

y= 4

so your complete answer is ( -3, 4)

RELATED: